2012
DOI: 10.3389/fnins.2012.00010
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Synthesis in the Nervous System: Implications for Myelination and Myelin Repair

Abstract: Progesterone is well known as a female reproductive hormone and in particular for its role in uterine receptivity, implantation, and the maintenance of pregnancy. However, neuroendocrine research over the past decades has established that progesterone has multiple functions beyond reproduction. Within the nervous system, its neuromodulatory and neuroprotective effects are much studied. Although progesterone has been shown to also promote myelin repair, its influence and that of other steroids on myelination an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
111
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(130 citation statements)
references
References 257 publications
4
111
0
4
Order By: Relevance
“…[9][10][11][12][63][64][65][66][67] We have demonstrated in previous works that chronic PROG administration increases the expression of transcription factors that define oligodendrocyte linage, such as Olig2 and Nkx2.2 after spinal cord transection. 21,29 In the present work, we report that PROG treatment reduced the loss of oligodendrocyte numbers and MBP immunoreactivity produced by SCI.…”
Section: Prog Reduced Secondary Injury and White Matter Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][63][64][65][66][67] We have demonstrated in previous works that chronic PROG administration increases the expression of transcription factors that define oligodendrocyte linage, such as Olig2 and Nkx2.2 after spinal cord transection. 21,29 In the present work, we report that PROG treatment reduced the loss of oligodendrocyte numbers and MBP immunoreactivity produced by SCI.…”
Section: Prog Reduced Secondary Injury and White Matter Pathologymentioning
confidence: 99%
“…7,8 Progesterone (PROG) could represent a good candidate for therapy, because it is neuroprotective, promyelinating, and antiinflammatory in pathologies of peripheral and central nervous systems. [9][10][11][12] Specifically, in experimental brain trauma, PROG reduces edema and inflammatory cytokines, prevents neuronal loss and mitochondrial dysfunction, and improves functional outcomes. [13][14][15] This has permitted the development of two Phase II clinical trials that have recently shown significant improvements in patients with traumatic brain injury receiving PROG.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as demonstrated in experimental models of several neurodegenerative disorders, the administration of neuroactive steroids is able to favor several protective/reparative processes like inhibition of neuronal death, promotion of neurogenesis, and myelination, as well as reduction of neuroinflammation (Brinton & Wang 2006, Garcia-Segura & Balthazart 2009, Melcangi et al 2011, Kipp et al 2012, Panzica et al 2012, Schumacher et al 2012. Intriguing is the modulation of this last process.…”
Section: Introductionmentioning
confidence: 99%
“…19 Perhaps in the present experiments progesterone facilitated the release of trophic factors from nearby Schwann cells. 31,32,[45][46][47] Nerve sectioning plays a fundamental role in aberrant innervation, since it occurred even in animals implanted with silicone tubes. In our study, the synaptic connectivity between the nerve supply to the gastrocnemius muscle and the muscle itself seemed to be functional.…”
Section: Discussionmentioning
confidence: 99%